Effect of forage sorghum hybrids varying in berry size on berry processing score and in situ starch digestibility - Douglas Duhatschek; Jourdan Bell; Luiz F. Ferraretto; Diego Duretto; John Goeser; Elizabeth Coons; Jason K. Smith; Sushil Paudyal; Juan M. Piñeiro (JDS Communications)
Water scarcity threatens the production of forages used to feed lactating dairy cows. Utilizing water efficient crops is key for dairy farms trying to mitigate drought and forage scarcity risks. Forage sorghum is a water-efficient crop with the potential to partially replace corn silage. However, challenges with processing forage sorghum berries have resulted in poor starch digestibility and decreased milk production of lactating dairy cows compared with those fed with corn silage. Consequently, this has prevented its adoption by dairy farmers. The objective of this study was to evaluate if a 1.70-mm berry processing score (BPS1.70) and ruminal in situ starch digestibility at 7 h (isSD7) would increase when harvesting forage sorghum with larger berry size compared with regular berry sized hybrid. Two forage sorghum hybrids (F10 and F24) were seeded in 5 plots blocked by the spans across the center irrigation pivot in a randomized complete block design. The F10 hybrid had average size berries; only 41.7% of intact berries were retained above a 3.35-mm sieve. Conversely, the F24 hybrid was genetically developed to produce a larger whole berry size and retained 90% of intact berries above a 3.35-mm sieve. With larger berries, the proportion of starch for the F24 increased almost 3 percentage units compared with F10 (26.6% and 23.9%, respectively). However, BPS1.70 and isSD7 were not different. The study suggests that although increasing berry size may increase starch content, it does not necessarily increase BPS1.70 and isSD7, at least for the berry size difference tested and harvested with kernel processors and settings commonly used to process corn.